2015
DOI: 10.1007/s13280-015-0673-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial trends of PCBs, DDTs, HCHs, and HCB in Swedish marine biota 1969–2012

Abstract: In the 1960s, the Baltic Sea was severely polluted by organic contaminants such as PCBs, HCHs, HCB, and DDTs. Elevated concentrations caused severe adverse effects in Baltic biota. Since then, these substances have been monitored temporally and spatially in Baltic biota, primarily in herring (Clupea harengus) and in guillemot (Uria aalge) egg, but also in cod (Gadus morhua), perch (Perca fluviatilis), eelpout (Zoarces viviparous), and blue mussel (Mytilus edulis). These chemicals were banned in Sweden in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…In SAM, the significant increment of contaminant levels in polychaete tissues during winter was related to differences observed in lipid percentage and partly to OCPs and PCBs increase in close sediments. A winter increment of OCPs and PCBs levels was also found in other aquatic species (Milun et al, 2016), and it is often associated with changes in the inputs of organic contaminants from diffuse sources in the whole watershed by precipitation and runoff process (Nyberg et al, 2015). In addition, seasonal lipid differences may be related to physiological fluctuations observed in some nereid species by changes in gametogenic cycle and diet (Luis and Passos, 1995).…”
Section: Discussionmentioning
confidence: 95%
“…In SAM, the significant increment of contaminant levels in polychaete tissues during winter was related to differences observed in lipid percentage and partly to OCPs and PCBs increase in close sediments. A winter increment of OCPs and PCBs levels was also found in other aquatic species (Milun et al, 2016), and it is often associated with changes in the inputs of organic contaminants from diffuse sources in the whole watershed by precipitation and runoff process (Nyberg et al, 2015). In addition, seasonal lipid differences may be related to physiological fluctuations observed in some nereid species by changes in gametogenic cycle and diet (Luis and Passos, 1995).…”
Section: Discussionmentioning
confidence: 95%
“…The trend exemplified by the seal stocks is representative for overall conditions for hazardous substances in Swedish seas. A comprehensive study of toxins (PCBs, DDTs, HCHs and HCB) in marine biota in Swedish seas found that between 1969 and 2012 the levels decreased significantly, showing that measures taken in the form of bans and restrictions on different substances in the 1970s and 1980s have had the desired effect (Nyberg et al 2015). While levels in the Baltic Sea remain elevated, with considerable variation between different substances and areas, the overall trend is one of recovery.…”
Section: Mixed Messages: the Empirical Evidencementioning
confidence: 99%
“…In recent years, marine scientists have recorded more diverse developments in Swedish seas than are described by an overall declensionist narrative. Data show trends of interrupted decline, variability and even recovery, taking place at least partly in response to effective policy and legislation, such as bans on several toxins (Nyberg et al 2015). Nevertheless, beyond the scientific realm, an overarching declensionist narrative tends to persist.…”
Section: Introduction: a Narrative Of Declinementioning
confidence: 99%
“…mollusks (Sericano et al, 2014;Grotti et al, 2016), fish (Nyberg et al, 2015;Cincinelli et al, 2016), sea birds (Elliott and Elliott, 2013;Miller et al, 2015) and mammals (Lam et al, 2016) have been used as biomarkers to trace temporal trends of POPs (Table 2). Monitoring programs such as "Mussel Watch" of the US from 1986, "Swedish National Monitoring Program for Contaminants in Marine Biota" from 1969 and "Environmental Specimen Bank" initiated by Germany from the 1980s have conducted long term observations for coastal environmental changes (Sericano et al, 2014;Nyberg et al, 2015;Grotti et al, 2016). Decreases of DDTs, PCBs, HCHs and PBDEs and increases of HBCD and PFAAs were reflected by coastal organisms.…”
Section: Temporal Trendmentioning
confidence: 99%